Implementation of hospital antimicrobial stewardship programmes in low- and middle-income countries: a qualitative study from a multi-professional perspective in the Global-PPS network - Ines Pauwels; Ann Versporten; Diane Ashiru-Oredope; Silvia Figueiredo Costa; Herberth Maldonado; Ana Paula Matos Porto; Shaheen Mehtar; Herman Goossens; Sibyl Anthierens; Erika Vlieghe (Antimicrobial Resistance and Infection Control)
Abstract Background Hospitals in low- and middle-income countries (LMIC) face context-specific challenges in implementing antimicrobial stewardship (AMS) programmes. The Global Point Prevalence Survey (Global-PPS) project has established a network of hospitals across 90 countries, using point prevalence surveys to monitor antimicrobial use and guide AMS activities. However, little is known about AMS implementation in these hospitals. Using qualitative research, we aim to explore the implementation process in LMIC hospitals within the Global-PPS network and the factors influencing it, identify potential implementation strategies, and evaluate the role of Global-PPS in this process. Methods A qualitative study was conducted using semi-structured online interviews with healthcare workers (HCWs) involved in AMS in LMIC hospitals within the Global-PPS network. Participants were selected using a combination of convenience and purposive sampling and included clinicians, microbiologists, pharmacists, and nurses. Interviews followed a topic guide based on the integrated checklist of determinants of practice (TICD Checklist). Transcripts were analysed using a combination of inductive and deductive thematic analyses. Findings Twenty-two HCWs from 16 countries were interviewed. Hospitals were in different stages of the AMS implementation process at the time of the study, from pre-implementation to institutionalisation of AMS as part of the continuous quality improvement process. While the Global-PPS provided a valuable tool for education and implementation, contextual barriers often hindered the translation of findings into targeted interventions. Four themes influenced AMS implementation, “institutional support and resource allocation”, “AMS team functioning, roles, and expertise”, “adoption and integration of AMS recommendations”, and “data-driven decision-making” as a cross-cutting theme. Key determinants included AMS team competencies, multidisciplinary teams, sustainable funding and leadership support, diagnostic capacity, and reliable data to inform interventions. We also identified various strategies employed by local AMS teams to enhance implementation. Conclusions This study examines AMS implementation in LMIC hospitals in the Global-PPS network and identifies key determinants. AMS teams address challenges through task shifting, local engagement and ownership. While empirical evidence on the effectiveness of these strategies is limited, these insights can guide future AMS interventions and studies within LMIC hospitals. Strengthening AMS requires bridging the gap between measurement and action and expanding research on behaviour change.